Share Prices and Total Shares Before and After Covid-19 Announcement in Consumer Goods Industry - An Suci Azzahra; Ayu Wirdha Ningsih; Prana Ugiana Gio (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research aimed to analyze the reaction of stock prices and the total shares before and after the announcement of the covid-19 in the Consumer Goods Industry Sector on the Indonesia Stock Exchange. Research methodology: Data were acquired from the website www.idx.co.id  with the sample of 50 companies. The observation period was at 31 January and  31 March 2020. The method research was a comparative study. Data were analyzed through the Wilcoxon Signed Rank Test. Results: The results showed that the announcement of covid-19 had an effect on stock prices as seen from the value (2-tailed) is 0.000 < 0.05. Meanwhile, the Covid-19 announcement did not affect the total shares, as seen from the value (2-tailed) is 0.490 > 0.05. Limitations: This research only observed one research object. The observation period was at 31 January and  31 March 2020. That is only examined 1 company sector, besides, it only compared two variables. Contribution: The companies must change their sales strategy to be able to raise stock prices and Total Shares.